Career Pursuit in Taxation Driven by Education and Motivation Factors: Pursuit Karir dalam Perpajakan Dipicu oleh Biaya Pendidikan dan Motivasi - Noviyanti, Dina; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2024)
Background: The complexity of taxation necessitates highly skilled professionals. Specific Background: Despite demand, factors influencing students' interest in taxation careers are underexplored. Knowledge Gap: Previous studies have not adequately examined the combined effects of educational costs, social motivation, career motivation, and tax knowledge on career choices in taxation. Aims: This research investigates how these factors impact the intention to pursue a tax brevet. Results: Using quantitative analysis and Partial Least Squares (PLS) on a sample from Muhammadiyah University of Sidoarjo, the findings indicate that educational costs, social motivation, career motivation, and tax knowledge significantly influence students' interest in taxation careers, highlighting both direct and indirect relationships. Novelty: This study integrates various motivational factors affecting career aspirations in taxation. Implications: The results emphasize the need for tax certificate training programs to enhance accounting graduates' expertise, making iTax ibrevet training essential for aspiring accountants in the taxation field. Highlights : Significant influence of educational costs on career interest in taxation. Integration of motivational factors impacts students' decisions in pursuing tax-related careers. Importance of tax certificate training programs for enhancing accounting graduates' expertise. Keywords: Taxation, Education Costs, Motivation, Tax Knowledge, Career Aspirations